Effect on Ocean Noise: Nyepi, a Balinese Day of Silence - Rob Williams; Christine Erbe; I Made Iwan Dewantama; Gede Hendrawan (Oceanography, 2018)
Taking advantage of a religious holiday called Nyepi that curtailed human activities for one day, we recorded acoustic noise levels for one week in shallow waters of a little-trafficked area west of Bali below the Denpasar airport flight path (Figure 1). Sound is as important to many marine organisms as vision is to humans. From the song of the humpback whale to the exquisite sonar system of the killer whale, many marine vertebrates have evolved sophisticated systems for sending and receiving acoustic signals to facilitate vital life functions. Coral reef fish sing in a dawn chorus, much as songbirds do (McCauley and Cato, 2000).